APLIKASI TIKTOK DI KALANGAN MAHASISWA FAKULTAS ILMU BUDAYA UNIVERSITAS HALU OLEO - Selpiana Selpiana; Wa Ode Winesty Sofyani (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to know and describe how the TikTok application is used among FIB UHO students, and what the impact of the TikTok application is on students at FIB UHO. The method in this study is a qualitative research method with data collection methods combining involved observation techniques (observation participation) and in-depth interviews (in-depth interviews). The results show that the use of the TikTok application among FIB UHO students is as follows: TikTok content that is useful, as a means of socializing, has interesting features, as a medium of expression, a means of communicating, following trends, and as a lifestyle. Meanwhile, the impact of the TikTok application on FIB UHO students is divided into two, namely the positive impact and the negative impact. The positive impacts are: sharing information, can encourage student creativity, updating information and as a learning tool. The negative impact is: reducing the quality of student sleep, and can inhibit other work and waste quotas.